EFEKTIVITAS PELAYANAN PEMADAMAN KEBAKARAN OLEH UNIT PELAKSANA TEKNIS DINAS PEMADAM KEBAKARAN DI KABUPATEN CIAMIS: Array - Devi Damayanti; Neti Sunarti; Otong Husni Taufiq (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Based on preliminary stewardship results, it is known that the effectiveness of fire fighting services is not yet effective. Starting from these problems, the formulation of the problem in this study can be formulated as follows: 1) How is the effectiveness of fire fighting services by the UPT Fire Department in Ciamis Regency ?; 2) What are the obstacles in the Effectiveness of Fire Fighting Services by the Fire Service Unit in Ciamis Regency ?; 3) How are the efforts to overcome obstacles in the Effectiveness of Fire Fighting Services by the Fire Service Unit in Ciamis Regency? The research method used in this research is to use a qualitative approach. The sampling technique used was purposive sampling. The data collection techniques include literature study, field study (interview observation) and documentation study. Data analysis techniques, namely from interviews, observations that have been written in field notes, personal documents, official documents, pictures, photos and so on. Based on the research results, it was found that: 1) The effectiveness of fire fighting services by the Technical Implementation Unit of the Fire Service in Ciamis Regency has not been implemented optimally. 2) Obstacles in realizing the effectiveness of blackout services include: officers who have not attended training or training, there is a lack of human resources, limited personal protective equipment for officers, and low understanding of the community regarding damkar services, which have not been carried out optimally because the post has not been established. firefighters in every sub-district or at least 9 sub-districts in Ciamis Regency, officers are less active in providing information or socializing to the community so that the public's understanding is low about the services of the Ciamis District Fire Brigade Regional Technical Implementation Unit. 3) Efforts to overcome the obstacles faced, namely the establishment of the WMK Damkar Post, Provision of Personal Protection Equipment for officers, Increasing the number of firefighters, Education and training of rescue workers, Training / simulations and outreach for fire volunteer communities, Forming fire fighting assisted communities, provision of competent experts in the preparation of fire management operational plan documents and public discussions of the Fire Protection System Master Plan, Inspection Officer Education and Training.